Impacts of site aridity on intra-annual radial variation of two alpine coniferous species in cold and dry ecosystems - Junzhou Zhang; Xiaohua Gou; Yuetong Wang; Qipeng Sun; Junjun Liu; Fang Wang; Min Xu; Jiqin Yang; Patrick Fonti (Ecological Indicators, 2024)
Climate change alters regional aridity and species composition in dryland ecosystems. However, the effect of varying aridity and species-specific responses on tree growth remains unclear. Here, we used high-resolution dendrometers to analyze the climatic factors controlling stem diameter variation in two alpine coniferous species, Qilian juniper (Juniperus przewalskii) and Qinghai spruce (Picea crassifolia), in their eastern- and western-most distributions (two species × two sites) in the Qilian Mountains during the 2018–2021 growing seasons. We observed species-, site-, and year-specific differences in growth phenology and radial growth dynamics. Juniper had early growth onset and cessation, but short growing season compared to spruce. Trees in the eastern sites showed earlier growth onset, later cessation, and a much longer growing season than those in the western sites for both species. Daily stem growth revealed similar responses for both species and site aridity, with daily vapor pressure deficit, maximum temperature, and solar radiation negatively, and relative humidity and precipitation positively affecting stem increments. However, when observation was extended to 7 or 21 days, the effect of precipitation on stem increments became weak or negligible in the wetter eastern sites, while continuing in the arid western sites. Further, soil water content appeared to have an impact on growth in the arid western site for both species. These results were confirmed by linear mixed-effects models, which revealed that site-aridity play an important role on tree stem variation, especially in junipers. Our results suggest that although short-term atmospheric water conditions influence radial stem variation, intra-annual tree growth still depends on soil water availability in drylands. Our findings provide new evidence of potential uses of dendrometers to measure environmental stress on tree growth and reveal that site aridity and species influence tree growth at different time scales in cold and arid ecosystems.